Semiquantitative fecal calprotectin test in postinfectious and non-postinfectious irritable bowel syndrome: cross-sectional study - David, Liliana-Elisabeta; Surdea-Blaga, Teodora; Dumitrascu, Dan-Lucian (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: The presence of a certain degree of inflammation in the gut wall is now ac-cepted in irritable bowel syndrome (IBS). Fecal calprotectin is considered to be a reliable test for detecting intestinal inflammation. Our aim was to assess the presence of inflammation in postinfectious IBS (PI-IBS), compared with non-postinfectious IBS (NPI-IBS). A secondary objective was to determine the usefulness of a rapid fecal calprotectin test in inflammatory bowel diseases (IBD). DESIGN AND SETTING: This was a cross-sectional study. Patients with IBS and IBD at a single tertiary gastroenterology center were prospectively included in this study. METHODS: 116 patients with Rome III IBS score (76 females; 48 ± 12 years) were investigated; 24 patients (15 females) had PI-IBS. Intestinal inflammation was assessed using the semiquantitative fecal calprotec-tin test. The results were expressed as T1, T2 or T3 according to the severity of inflammation (< 15 µg/g; 15-60 µg/g; > 60 µg/g). Using the same test, we evaluated 20 patients with IBD (12 males; 47 ± 13 years). RESULTS: None of the patients with IBS had a T2 or T3 positive test. Among PI-IBS patients, 33% had a T1 positive test. Among NPI-IBS patients, 9.8% had a T1 positive test, which was significantly different to PI-IBS. The calprotectin test was positive in all IBD patients: 80% with T3, 10% with T2 and 10% with T1. CONCLUSIONS: Using a semiquantitative test for fecal calprotectin, positive tests were more frequent in PI-IBS patients than in NPI-IBS patients.